Garvicin A, a Novel Class IId Bacteriocin from Lactococcus garvieae That Inhibits Septum Formation in L. garvieae Strains - Maldonado-Barragán, Antonio (American Society for Microbiology, 2013)
Lactococcus garvieae 21881, isolated in a human clinical case, produces a novel class IId bacteriocin, garvicin A (GarA), which is specifically active against other L. garvieae strains, including fish- and bovine-pathogenic isolates. Purification from active supernatants, sequence analyses, and plasmid-curing experiments identified pGL5, one of the five plasmids found in L. garvieae [M. Aguado-Urda et al., PLoS One 7(6):e40119, 2012], as the coding plasmid for the structural gene of GarA (lgnA), its putative immunity protein (lgnI), and the ABC transporter and its accessory protein (lgnC and lgnD). Interestingly, pGL5-cured strains were still resistant to GarA. Other putative bacteriocins encoded by the remaining plasmids were not detected during purification, pointing to GarA as the main inhibitor secreted by L. garvieae 21881. Mode-of-action studies revealed a potent bactericidal activity of GarA. Moreover, transmission microscopy showed that GarA seems to act by inhibiting septum formation in L. garvieae cells. This potent and species-specific inhibition by GarA holds promise for applications in the prevention or treatment of infections caused by pathogenic strains of L. garvieae in both veterinary and clinical settings.